2022
DOI: 10.3389/fneur.2021.806516
|View full text |Cite
|
Sign up to set email alerts
|

Myoclonic Epilepsy: Case Report of a Mild Phenotype in a Pediatric Patient Expanding Clinical Spectrum of KCNA2 Pathogenic Variants

Abstract: We report on the rare case of a male toddler presenting with myoclonic epilepsy characterized by daily episodes of upward movements of the eyebrows, and myoclonic jerks of both head and upper limbs. In addition, the child showed speech delay, tremors, and lack of motor coordination. Next Generation Sequencing analysis (NGS) performed in trio revealed in the proband the c.889C>T de novo missense variant in the KCNA2 gene in heterozygous state. This is the first case of myoclonic epilepsy in a toddler due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…31 Seizures of this phenotype have also been controlled using valproate sodium (VPA) in combination with ethosuximide. 32 In addition to epilepsy, KCNA2 variants have been identified in other diseases in recent years. Canafoglia et al reported one male patient carrying a KCNA2 GOF variant who presented with only progressive myoclonus epilepsy (PME).…”
Section: Key Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Seizures of this phenotype have also been controlled using valproate sodium (VPA) in combination with ethosuximide. 32 In addition to epilepsy, KCNA2 variants have been identified in other diseases in recent years. Canafoglia et al reported one male patient carrying a KCNA2 GOF variant who presented with only progressive myoclonus epilepsy (PME).…”
Section: Key Pointsmentioning
confidence: 99%
“… 31 Seizures of this phenotype have also been controlled using valproate sodium (VPA) in combination with ethosuximide. 32 …”
Section: K V Channel‐related Genes and Epilepsymentioning
confidence: 99%
See 1 more Smart Citation